Self-medication practices versus health of the community - Dutta, Ruma; Raja, Dinesh; R., Anuradha; Dcruze, Lawrence; Jain, Timsi; P., Sivaprakasam (International Journal Of Community Medicine And Public Health, 2017)
Background: Self-medication is a common practice worldwide and the irrational use of drugs is a cause of concern. Self-medication involves the use of medicinal products by the individuals to treat self-recognized disorders or symptoms, or the intermittent or continuous use of a medication prescribed by a physician for chronic or recurring diseases or symptoms. The objectives of the study were to find out the prevalence of self-medication practices in the community; to describe the common conditions where self-medication is practiced. Methods: A community based cross sectional study was conducted in a rural population at Kuthambakkam village, Tamil Nadu from February 2015 to July 2015. This village falls under the rural field practice area of Department of Community Medicine, Saveetha Medical College and hospital, Thandalam. There were 1175 households in this village of which 165 households were identified for the study purpose using simple random sampling technique. Statistical analysis: Data entry and analysis was done using SPSS version 16 software. Descriptive statistics were calculated for background variables, attitude and practices of self-medication. Results: The study was conducted in 165 households in Kuthambakkam village, the rural field practice area of Department of Community Medicine, Saveetha Medical College. The median age of the study participants was 38 years. The minimum age was 17 and maximum was 77 years. 73 (44.2%) of study subjects reported having health problems currently. Of them, 76.7% replied they consulted a doctor for their problem, 17.8% resorted to self-medication and rest 5.5% took native treatment at home. Conclusions: It is imperative to address the practice of self-medication among the people in the age of growing drug resistance being reported. Periodic studies on the knowledge, attitude and practice of self-medication may give an insight into the pattern of drug use among the people.